Potential of Crude Protease of Bacillus Sp. HSFI-9 ss Anticoagulant Agent and Meat Tenderizer - Izza, Naimatul; Saptaningtyas, Ragil; Stalis Norma Ethica; Kartika, Aprilia Indra (poltekkes kemenkes mataram, 2025)
Some proteases act as thrombolytic enzymes to destroy the abnormal blood clot in the body called a thrombus, a leading cause of mortality associated with cardiovascular disease (CVD). In addition, the enzyme may also hydrolyze the meat’s proteins into simple amino acids, causing the meat to become tender. The study's aim was to analyze the potential of the crude protease of Bacillus sp. HSFI-9 is an anticoagulant agent and meat tenderizer. The anticoagulant test of crude protease HSFI-9 on venous blood samples was performed by measuring the clotting time compared to control (10% EDTA) by the Lee-White method. Protein profiles of beef, chicken, and tuna were analyzed before and after immersion in the crude protease of Bacillus sp. HSFI-9 in concentration of 30% v/v for 3 hours based on Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) method. The anticoagulant test screening showed that the crude protease of Bacillus sp. HSFI-9 was able to prolong the blood clotting time even though its anticoagulant activity was still less than that of 10% EDTA (a commercial anticoagulant agent used as a positive control). The SDS-PAGE results indicated that soaked beef and chicken using crude protease from Bacillus sp. HSFI-9 could hydrolyze the meats’ proteins by denaturing them into smaller molecules, indicated by the appearance of new minor protein bands and the disappearance of major ones. It can be concluded that the crude protease of Bacillus sp. has potential as an anticoagulant agent and a meat tenderizer.